1998
DOI: 10.1159/000009954
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Accuracy of Transvaginal Sonography for the Assessment of Retained Products of Conception After Spontaneous Abortion

Abstract: Transvaginal sonography (TVS) was used to assess uterine contents in 100 consecutive subjects presenting with a diagnosis of spontaneous abortion. TVS assessments were correlated with findings at subsequent evacuation of retained products of conception (ERPC). There was a strong correlation between the weight of the surgical specimen at ERPC with both the sagittal (r = 0.76; p < 0.05) and transverse (r = 0.73; p < 0.05) plane area measurements of the uterine cavity. Combining the 2 sonographic measurements inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Most of the literature is based on grayscale sonographic features that include the following: (1) focal echogenic endometrial mass; (2) thickened endometrium; (3) complex endometrial fluid 9–14, 19–25. Of these features, the most useful predictor of RPOC is reported to be a focal echogenic mass in the endometrium 10, 13.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the literature is based on grayscale sonographic features that include the following: (1) focal echogenic endometrial mass; (2) thickened endometrium; (3) complex endometrial fluid 9–14, 19–25. Of these features, the most useful predictor of RPOC is reported to be a focal echogenic mass in the endometrium 10, 13.…”
Section: Discussionmentioning
confidence: 99%
“…The complete miscarriage was defined as an empty uterus or homogenous intrauterine dimension measuring <11 cm 2 (sagittal plus transverse plane) on transvaginal ultrasound examination. 21 The clinical symptomatology of miscarriage and its complications from treatment, women's satisfaction and the psychological impact after different treatment modalities were also evaluated.…”
Section: Interventionsmentioning
confidence: 99%
“…In contrast to these studies, other reports claim that ultrasound is a good diagnostic tool for assessment of residual postabortion remnants. Chung et al 25 reported that transvaginal sonography was accurate for assessment of retained products of conception after spontaneous abortion. In this report, a strong correlation was found between the weight of the surgical specimen at evacuation and the extent of the findings in the uterine cavity measured via sonography.…”
Section: Discussionmentioning
confidence: 99%